ESBL E coli and P. aeruginosa Resistance to Ceftolozane-Tazobactam in a Patient with a Liver Abscess. The Search for an Omnipotent Antibiotic Goes On! - Teleb, Mohamed; Soto-Ruiz, Enrique; Dominguez, Delfina C.; Antony, Suresh (Infectious Disorders - Drug Targets, 2018)
Multi drug resistant (MDR) Pseudomonas aeruginosa and Extended- Spectrum-lactamase (ESBL) Enterobacteriaceae are becoming an increasing difficult clinical problem. Immediate resistance to some of the new antimicrobials such as ceftolozane/tazobactam is unusual and is due to a variety of mechanisms such as hyper-production of inactivating enzymes and gene mutation. In addition, previous antimicrobial administration is a well-recognized risk factor to develop resistance. We present a patient with a liver abscess where the organism was resistant to ceftolozane/tazobactam resulting in a poor clinical outcome.
Keywords: gram negative bacteria